Approach to Plagiarism Detection in Programming Assignments - Algabri, Malek; Alhrazi, Firdaus (Journal of Engineering and Technological Sciences - JOEATS, 2025)
People tend to shortcut ways that save them time and effort to do the tasks required by them, either by taking tasks ready-made online, or stealing someone’s work as their own. Since                everything now is connected to the Internet, there is a very high potential of duplicating or stealing someone else’s work, which is known as plagiarism. With the advancement of technology, it has become quite simple to do all tasks through the Internet. Plagiarism is the copying of other people’s ideas and actions; it  is considered a crime. Plagiarism occurs due to laziness, fear of failure, and the desire to perform the required tasks without fatigue or effort. In this paper, a methodology for detecting plagiarism in programming tasks, in particular in the visual programming category using deep learning and machine learning algorithms is proposed. Also, a solution has been proposed to detect plagiarism in the source code and interfaces that pertain    to programming assignments.